Influence of professional commitment and locus of control to the ethical sensitivity of auditors - Banda, Falentina Lucia; Londa, Yulita; Soleiman, Iriany Dewi; Rambut, Kanisius (International research journal of management, IT and social sciences, 2021)
This article is intended to explore the influence of professional commitment and locus of control on the Ethical Sensitivity of the Auditors in the inspectorate sector in the regencies or city, especially in Flores Island. It promotes the issue of the influences of professional commitment and locus control to the ethical sensitivity of the auditors who dedicate to the inspectorate sector of the regencies or city. It is assumed that supervision and inspection is the task of the inspectorate in the Regencies or City. The results of supervision and inspection can increase public financial accountability and improve good governance. The purpose of the study was to determine the effect of professional commitment and locus of control on the ethical sensitivity of auditors who work in the Inspectorate sectors in three regencies in Flores island. The population and sample in this study were 46 auditors who work in the Inspectorate in Flores island. The sample used is a saturated census in which the entire population is sampled. Multiple linear regression analysis was used in this study. The results of the study prove that professional commitment and locus of control have a significant effect on the ethical sensitivity of auditors in Flores.